The Relationship between Psychosocial Stress on The Quality of Life and Self-Control in Adolescent Girls - Jumrah Jumrah; Stang Stang; Nurlaila Fitriani; Andi Agus Mumang; Mukminah Al Mukarramah (Direktorat Politeknik Kesehatan Makassar, 2025)
Introduction: High academic pressure affects adolescents’ emotional and social well-being, resulting in a decline in their overall quality of life and impacting their self-control abilities. Objective: This study aimed to analyze the relationship between stress on the quality of life and self-control of adolescents. Methods: This was a cross-sectional study. The sample consists of 225 11th-grade female students, determined using the Lemeshow formula with an α=5% margin of error. Simple random sampling was employed. The instruments used were the Perceived Stress Scale (PSS) questionnaire, WHOQOL-BREF questionnaire, and Self-control Competency Scale questionnaire. Data were analyzed using SPSS version 16 with a chi-square test. Results: Most respondents experienced moderate stress (188 people, 83.6%), most female students had a low quality of life (160 people, 71.1%), and had moderate self-control (188 people, 83.6%). There is a significant correlation between stress and the quality of life of adolescent girls (P=0.000<0.05) and self-control (P=0.000<0.05). Conclusion: High stress is associated with low quality of life and self-control in adolescent girls.